Optimal Tuning of PD controllers using Modified Artificial Bee Colony Algorithm - Hashim, M. R.; A. K., Hyreil; Tokhi, M. O. (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
This paper presents an investigation of PD controller tuning using a modified artificial bee colony algorithm (MABC). The main purpose of this work is to apply and investigates the performance of MABC in tuning the PD controller of single link manipulator system (SLMS) in comparison with the original ABC. The objective of the MABC algorithm is to minimize the error by using mean square error (MSE) as an objective function. The proposed algorithm has also been tested in three benchmark functions with different dimensions to checked the robustness of the algorithm in different problems surface. The result shows that the MABC able to tune the controller to their best optimum value.